2021
DOI: 10.1001/jama.2021.21892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minimally Invasive Surfactant Therapy vs Sham Treatment on Death or Bronchopulmonary Dysplasia in Preterm Infants With Respiratory Distress Syndrome

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 32 publications
1
88
0
Order By: Relevance
“…In contrast, we found a substantial and sustained decline in BPD rates (ARD −10.7%) between 2010 and 2017, with BPD being defined as a requirement for supplemental oxygen to maintain arterial oxygenation of 90% or more at 36 weeks [25]. Employing a similar physiological definition of BPD, the recent multinational OPTIMIST-A trial demonstrated that surfactant administration without intubation was associated with a significantly reduced incidence of BPD in survivors [21]. The observed ARD (−7.8%) was very similar to that obtained by a previous meta-analysis comparing RCTs that randomized surfactant administration with or without endotracheal intubation (ARD −7.6%) [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we found a substantial and sustained decline in BPD rates (ARD −10.7%) between 2010 and 2017, with BPD being defined as a requirement for supplemental oxygen to maintain arterial oxygenation of 90% or more at 36 weeks [25]. Employing a similar physiological definition of BPD, the recent multinational OPTIMIST-A trial demonstrated that surfactant administration without intubation was associated with a significantly reduced incidence of BPD in survivors [21]. The observed ARD (−7.8%) was very similar to that obtained by a previous meta-analysis comparing RCTs that randomized surfactant administration with or without endotracheal intubation (ARD −7.6%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that the decline of BPD in infants of 24–27 weeks’ gestation might be related in part to the concomitant increase in the fraction of infants managed without endotracheal intubation. Less invasive ventilation may have further contributed to the decline of mortality observed, as suggested by the LISA meta-analysis [20], although LISA did not reduce the rate of death in the most recent OPTIMIST-A trial [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recently published OPTIMIST-A trial, a multicenter masked RCT that compared surfactant treatment using a thin catheter vs. sham treatment in preterm infants 25 to 28 6/7 weeks of gestation on CPAP, found no difference in the incidence of death or the composite outcome of death or BPD at 36 weeks' PMA between the two groups. The incidence of BPD in survivors was lower in the MIST group ( 47 ).…”
Section: Medications Used In Bpdmentioning
confidence: 82%
“…Most recently, the OPTIMIST-A trial assessed the effectiveness of surfactant administration via MIST in extremely preterm infants with RDS managed on CPAP. The overall composite BPD or death was not significantly reduced in the TCA group compared with CPAP alone (43.6 vs. 49.6%), while death was not significantly different (10 vs. 7.8%), BPD at 36 weeks' postmenstrual age was lower in the MIST group (37.3 vs. 45.3%) ( 62 ).…”
Section: Thin Catheter Administrationmentioning
confidence: 99%